Real-world feasibility and safety of neoadjuvant FOLFIRINOX in pancreatic ductal adenocarcinoma: a retrospective single-center study - D’Haens, Soetkin; Billiet, Antoon; Topal, Halit; Topal, Baki; Van Herpe, Filip; Dekervel, Jeroen (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Neoadjuvant chemotherapy in non-metastatic pancreatic ductal adenocarcinoma (PDAC) is increasingly being studied and used in clinical practice. However, this strategy is associated with significant toxicity, biopsy-related and biliary complications and possible treatment delay. We aimed to assess the feasible number of cycles of neoadjuvant (modified) FOLFIRINOX and the real-world toxicity, to inform an optimal interventional trial design.Methods: In this descriptive monocentric study, we identified patients with borderline resectable or locally advanced PDAC, treated with upfront (m)FOLFIRINOX from 2020 to 2023. We analyzed patient and disease characteristics, dosing of therapy, occurrence of serious adverse events (SAEs) and reasons for discontinuation, and compared this data with available evidence in the literature.Results: Eighty-one patients were included. Median age was 65, most patients had an ECOG performance status of 0. 62.5% of tumors were borderline resectable, the others were locally advanced. 49 patients (60.5%) received mFOLFIRINOX, 32 (39.5%) received FOLFIRINOX and the median number of cycles administered was six. Most common reasons for discontinuation were surgery (n=45, 55.6%) and persistently inoperable or progressive disease (n=25, 30.9%), with toxicity accounting for a much smaller proportion (n=5, 6.2%). Global dose intensities gradually decreased over time. Dose reduction was necessary in 43 patients (53%), and 37 patients (45.7%) needed inpatient care. However, supportive care measures allowed most patients to overcome toxicity and finish the planned treatment cycles.Conclusions: With adequate supportive care and dose modifications, the majority of patients were able to complete the assigned chemotherapy cycles. Eight cycles of mFOLFIRINOX appear feasible for most patients and may serve as an optimal regimen for evaluation in future interventional trials.